Heavy metals inhalation exposure analysis from particulate matter emitted from dry and wet recycling processes of waste electrical and electronic equipment. Issue 6 (12th June 2019) - Lasithiotakis, Michael; Psanis, Christodoulos; Triantafyllou, Eleni; Nikolaou, Panagiota; Kouvarakis, George; Michalopoulos, Nikolaos; Sinioros, Panagiotis; Biskos, George
Abstract: Waste electrical and electronic equipment (WEEE) recycling processes produce aerosols that influence occupational health. This work is a characterization of aerosols and dust from dry and wet WEEE recycling processes in a small plant. A particle spectrometer measured size distributions of ultrafine particles whereas a deposition impactor collected aerosols for chemical analysis. Powders from milled printed circuit boards and from the cathode ray tube (CRT) processing line were additionally analyzed. Morphological characterization of the dusts by optical and electron microscopy also took place. All plant compartments are subject to aerosol concentrations during the work hours with highest concentration at 10 5 particles/cm 3 . The wet recycling technique was more efficient in retaining powders in the solid form than the dry technique. An exposure calculation and a risk assessment of an average worker were carried out. By the worst case scenario the total daily inorganic elements are 80.5 μg, mainly consisting of aluminium copper and iron. The exposure calculation and the risk assessment revealed that accumulation of aerosols in other compartments has a higher impact than the dry process itself. Results showed that for both methods pollutants concentrations were low, even in the worst‐case scenario examined.